2017
DOI: 10.1093/treephys/tpx013
|View full text |Cite
|
Sign up to set email alerts
|

Differences in functional and xylem anatomical features allow Cistus species to co-occur and cope differently with drought in the Mediterranean region

Abstract: A significant increase in drought events frequency is predicted for the next decades induced by climate change, potentially affecting plant species mortality rates and distributions worldwide. The main trigger of plant mortality is xylem hydraulic failure due to embolism and induced by the low pressures at which water is transported through xylem. As the Mediterranean basin will be severely affected by climate change, the aim of this study was to provide novel information about drought resistance and tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…Jacobsen et al (2005) found that the effect of vessel density on embolism resistance is due to its role in modifying fiber properties in wood. A reverse pattern was observed in the genus Cistus , where species with narrow vessels were found to be more prone to xylem embolism in the Mediterranean region (Torres-Ruiz et al ., 2017b). Gleason et al (2016) tested this trade-off across many angiosperms and gymnosperm species and found a positive correlation between hydraulic conductivity and P 50 and concluded that there is a weak tradeoff between hydraulic efficiency and safety among species.…”
Section: Discussionmentioning
confidence: 96%
“…Jacobsen et al (2005) found that the effect of vessel density on embolism resistance is due to its role in modifying fiber properties in wood. A reverse pattern was observed in the genus Cistus , where species with narrow vessels were found to be more prone to xylem embolism in the Mediterranean region (Torres-Ruiz et al ., 2017b). Gleason et al (2016) tested this trade-off across many angiosperms and gymnosperm species and found a positive correlation between hydraulic conductivity and P 50 and concluded that there is a weak tradeoff between hydraulic efficiency and safety among species.…”
Section: Discussionmentioning
confidence: 96%
“…When we considered only Eucalyptus species, additional patterns emerged; most notably, D h and maximum K s were related negatively to P 50 . This suggests that both metrics of the postulated trait coordination along an axis of hydraulic safety and efficiency, represented by embolism resistance and conduit diameter as referenced above (Cai & Tyree, 2010; Ellmore & Ewers, 1985; Hargrave et al, 1994), or as embolism resistance and maximum conductivity (Martínez‐Vilalta et al, 2002; Tyree et al, 1994; Zimmermann, 1983), which researchers have struggled to conclusively demonstrate (Gleason et al, 2016; Torres‐Ruiz et al, 2017), do emerge among closely related species—likely obscured by divergent environmental adaptations in the larger plant community.…”
Section: Discussionmentioning
confidence: 99%
“…the xylem pressure inducing 50% of PLC, were obtained by averaging the values of 13 to 15 samples per provenance. The P 50 value is commonly used as a proxy for tree drought resistance: the lower the P 50 value, the more drought tolerant the species (Delzon 2015, Torres-Ruiz, Cochard, Fonseca, et al 2017.…”
Section: Vulnerability To Embolismmentioning
confidence: 99%